Emerging evidence for FFLO states in layered organic superconductors (Review Article) - Beyer, R.; Wosnitza, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
In this short review, we report on the recently found growing experimental evidence for the existence of Fulde–Ferrell–Larkin–Ovchinnikov (FFLO) states in quasi-two-dimensional organic superconductors. At high magnetic fields aligned parallel to the conducting organic layers, we observe an upturn of the upper critical fieldbeyond the Pauli limit, as evidenced by specific-heat and torque-magnetization measurements. Inside the superconductingstate a second thermodynamic transition emerges. These features appear only in a very narrow angular region close to parallel-field orientation.